Design, Manufacturing and Testing of Small Shaking Table - H. Humaish, Asad; S. Shamkhi, Mohammed; K. Al-Hachami, Thualfiqar (International Journal of Engineering and Technology, 2018)
The seismic performance and the dynamic response of concrete gravity dams can be verified by several techniques. Both geotechnical centrifuge apparatus (under N-g values) and shaking table (under 1-g) are the commonly used techniques in the world. This paper deals with designing, manufacturing, and testing of small shaking table to investigate different geotechnical and engineering problems. The main body of the designed shaking table consists of steel frame (local iron) manufactured as a hollow box with steel plate, 6mm in thickness and one-direction movable platform (as a basket carrying the container of the model).  Inside this main box, all the mechanical parts that work as one system to generate the motion of the seismic wave with an acceleration that needed to the test.  The facilities of this shaking table, the movable base has a dimension of 0.8m x1.2m and the platform mass approximately 2 kN, the maximum allowable model weight of 10kN, the range of frequency from 0 to 20 Hz, the maximum acceleration amplitude of 1.2g and maximum displacement of 14mm. It can simulate only the single frequency motion (i.e. sinusoidal wave). The measured accelerations at different soil model level for the tested shaker under 0.6g sinusoidal waveform gave a reasonable prediction for the dynamic response and the amplification characteristics.